2012
DOI: 10.1007/s11136-011-0100-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of Spanish children with cystic fibrosis

Abstract: PurposeTo investigate (1) the contributions of sex, age, nutritional status- and physical-fitness-related variables on health-related quality of life (HRQOL) in Spanish children with cystic fibrosis, and (2) the agreement on HRQOL between children and their parents.MethodsIn 28 children aged 6–17 years, body mass index percentile, percentage body fat, physical activity, pulmonary function, cardiorespiratory fitness, functional mobility, and dynamic muscle strength were determined using objective measures. HRQO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 30 publications
5
50
0
5
Order By: Relevance
“…As we compared our Eastern European patients' HRQOL data to the counterparts from Western Europe, the United States and Australia [21][22][23][24][25], we found similar results. In view of limitations in Eastern European CF care, it is an interesting and important notification.…”
Section: Discussionsupporting
confidence: 55%
“…As we compared our Eastern European patients' HRQOL data to the counterparts from Western Europe, the United States and Australia [21][22][23][24][25], we found similar results. In view of limitations in Eastern European CF care, it is an interesting and important notification.…”
Section: Discussionsupporting
confidence: 55%
“…The low correlation between the and proxy-rating in this study has also been reported previously for Physical and Emotion domains [17,18]. The domains Emotion, Treatment Burden, Social, Body Image also showed no correlation, as seen in the Spanish study and the study by Havermans, et al [20,26]. The positive association between scores in Respiration domain and spirometry [16] have also been previously reported [16,26], thereby validating CFQ-14+ showing correlation between pulmonary function and Respiration domain.…”
Section: Fig 1 a Correlation Between Hrqol Scores (Adolescent's Formsupporting
confidence: 88%
“…The CFQ-R is the only patient-reported outcome instrument with versions for both children and the caregivers. It has been translated into 34 languages all over the world [17][18][19][20][21]. Our objective was to use CFQ-R to assess Quality of Life (QoL) in Indian children with CF.…”
mentioning
confidence: 99%
“…40,41 Of note, girls with CF have reported more emotional symptoms and greater pain, spend more time in the hospital than boys with a similar level of illness, [41][42][43] and have a worse prognosis than boys. [44][45][46][47][48] Our findings suggest that boys may emphasize taking responsibility for their treatments and maintaining a positive attitude, whereas some girls expressed the value of sharing responsibility for their health management with, for example, their parent or doctor.…”
Section: Discussionmentioning
confidence: 99%